2012
DOI: 10.1371/journal.pone.0050809
|View full text |Cite
|
Sign up to set email alerts
|

The Dermatan Sulfate Proteoglycan Decorin Modulates α2β1 Integrin and the Vimentin Intermediate Filament System during Collagen Synthesis

Abstract: Decorin, a small leucine-rich proteoglycan harboring a dermatan sulfate chain at its N-terminus, is involved in regulating matrix organization and cell signaling. Loss of the dermatan sulfate of decorin leads to an Ehlers-Danlos syndrome characterized by delayed wound healing. Decorin-null (Dcn−/−) mice display a phenotype similar to that of EDS patients. The fibrillar collagen phenotype of Dcn−/− mice could be rescued in vitro by decorin but not with decorin lacking the glycosaminoglycan chain. We utilized a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…A corresponding significant decrease in 3D tumor volume and viability was observed in 3D nodules grown under flow. These findings are consistent with the decreased proliferation that is a characteristic of EMT (30,32,(35)(36)(37) and the high attrition rates that metastatic nodules experience as they cope with the physical and biological stresses associated with colonizing distant sites (1,6,67,68 Fractal dimension (a ratio describing how an object fills space out to its maximum radius with a value of 1 describing a line and a value of 2 a circle) was used to quantify the morphological features of 3D tumors grown under flow versus nonflow conditions. Fractal dimension was significantly lower under flow (1.78 ± 0.01, n = 8 fields) than in nonflow (1.87 ± 0.01, n = 6 fields) conditions (P < 0.05), supporting the observation that flow induces morphological changes consistent with increased EMT in 3D tumors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A corresponding significant decrease in 3D tumor volume and viability was observed in 3D nodules grown under flow. These findings are consistent with the decreased proliferation that is a characteristic of EMT (30,32,(35)(36)(37) and the high attrition rates that metastatic nodules experience as they cope with the physical and biological stresses associated with colonizing distant sites (1,6,67,68 Fractal dimension (a ratio describing how an object fills space out to its maximum radius with a value of 1 describing a line and a value of 2 a circle) was used to quantify the morphological features of 3D tumors grown under flow versus nonflow conditions. Fractal dimension was significantly lower under flow (1.78 ± 0.01, n = 8 fields) than in nonflow (1.87 ± 0.01, n = 6 fields) conditions (P < 0.05), supporting the observation that flow induces morphological changes consistent with increased EMT in 3D tumors.…”
Section: Discussionsupporting
confidence: 86%
“…Decreased E-cadherin expression also is a hallmark of epithelial-to-mesenchymal transition (EMT) (26)(27)(28)(29)(30), a critical step in metastatic progression and a prognostic indicator of aggressive and refractory disease (31)(32)(33)(34)(35). Along with loss of E-cadherin, EMT is characterized by a range of molecular and morphological features, including the acquisition of a motile and mesenchymal phenotype with increased spindle-like morphology as well as increased expression of vimentin, an intermediate filament that maintains cell and tissue integrity and helps confer resistance to mechanical stress (30,32,(35)(36)(37). The cell-cycle regulator p27Kip1 modulates proliferation, motility, and apoptosis by inhibiting an array of cyclindependent kinases including cell-division control protein kinase 2 (CDC2) and also plays a role in cytoskeletal remodeling (38,39).…”
mentioning
confidence: 99%
“…Recently, the small non-coding microRNA149 has been linked to a new fine-tuning element of Fgf2-induced proliferation in endothelial cells by regulating the HS proteoglycan glypican (Chamorro-Jorganes et al, 2014). We have previously shown that the lack of decorin in skin led to the reduction of Ust and an impaired cell morphology in a 3D environment (Nikolovska et al, 2014;Jungmann et al, 2012), which could partially contribute to the delayed wound healing of the Dcn 2/2 mice (Järveläinen et al, 2006). We proved the importance of 2-O sulfation by showing that there was an impaired migration of 3T3 cells with a knockdown of Ust.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, PMNs derived from this mouse show increased adhesion to blood vessels during intravital microscopy (26). Whereas the decorin-de- (42,59). The CD3⑀ stimulation may lead to changes on the cell surface that result in a decrease of activity.…”
Section: Discussionmentioning
confidence: 81%
“…Purification and characterization of the biologically active decorin protein core were described before (41). Samples were analyzed as described before and had no detectable levels of endotoxins (42). The following substances were used: CS4S and CS6S (Sigma), murine recombinant cytokines IFN-␥ and TNF-␣ (R&D Systems), and mrCXCL-10 (eBiosciences).…”
Section: Methodsmentioning
confidence: 99%